Penguatan jejaring kerjasama pengurus Bumdes Desa Jatijajar sebagai upaya peningkatan relasi bisnis - Indah Anisykurlillah; Amir Mahmud; Nurdian Susilowati; Eka Rahmawati (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Riau, 2021)
The purpose of this community service activity is; first, the director and management of the Asung Daya Village Owned Enterprise (BUMDes) can conduct business negotiations. Second, the director and management of Asung Daya Village-Owned Enterprise can work on business relations to improve business relations. Community service activities are carried out in the form of socialization, training, and problem-solving business relations. The participants of the movement were the directors and administrators, as many as five people. BUMDes directors and management can understand the importance of business relations. They had not established business relationships with large companies in the surrounding villages and sub-districts before community service. With an understanding of business relations, the management began to formulate proposals for business relations with PT Coca Cola, Sosro, and Nissin. Of the three who continue to communicate intensively is PT Nissin. In addition, follow-up activities are carried out by establishing intensive communication so that it is hoped that good business relations will continue every year.